Determination Of Sun Protection Factor (SPF) Value Of Endophyte Fungi From Sendok Leaves (Plantago Major L.) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
Excessive exposure to UV rays can cause adverse effects on the skin, such as erythema, pigmentation, premature aging, and skin cancer. The use of sunscreen is an important protection for the skin from UV exposure. Sunscreen works by reflecting or absorbing UV rays, preventing them from reaching the skin. However, synthetic sunscreens may have potential side effects such as irritation and allergic reactions. Therefore, sunscreens made from natural ingredients are an alternative to synthetic sunscreens. One source of natural ingredients to replace synthetic sunscreen is the utilization of secondary metabolites from endophytic fungi. Endophytic fungi have potential as natural active ingredients in sunscreen because they can produce secondary metabolites similar to their host plants. This study evaluated the potential of endophytic fungi on spoon leaf plants as a natural sunscreen alternative. Endophytic fungi were cultivated in a PDA medium and then propagated in a PDB medium before extraction with ethyl acetate. Macroscopic and microscopic identification results showed that the two fungal isolates obtained belonged to the genus Aspergillus. Phytochemical tests confirmed the presence of flavonoids, alkaloids, and steroids in the extracts. Ethyl acetate extracts of Aspergillus sp. from spoon leaves showed that the extracts protected against ultraviolet rays, with the highest SPF value at a concentration of 500 ppm, namely 38.47 and 40, which falls into the ultra-protection category.